Group-works: exploring multiplex networks, leadership and group performance. Issue 4 (11th October 2019) - Yeow, Pamela; Dean, Alison; Tucker, Danielle; Pomeroy, Linda
Abstract : Purpose: The purpose of this paper is to explore the effect of "multiplex" (multiple overlapping) networks and leadership on group performance in a higher education setting. Design/methodology/approach: Using a combination of social network analysis and interviews, the authors employ a case study approach to map the connections between academic group members. This paper analyses the relationship between this mapping and academic performance. Findings: The authors identified two dimensions which influence group effectiveness: multiplex networks and distributed–coordinated leadership. Where networks are built across tasks, inter-relationships develop that lead to greater group performance. Practical implications: Where group members create a dense hive of interconnectivity and are active across all group tasks, and also informally, this increases the opportunity for knowledge sharing. When this is similarly experienced by a majority of group members, there is positive reinforcement, resulting in greater group effectiveness. Originality/value: This paper highlights the importance of the richness of formal ties in knowledge-intensive settings. This paper is the first to differentiate between formal connections between colleagues related to different tasks within their role. This suggests that dense configurations of informal ties are insufficient; they must be coupled with strong ties around formal activity and demonstrative leadership.